Customer Strategy Transformation Through CRM Innovation And Product Quality: Its Impact On Loyalty At Nou Coffee Shop: Transformasi Strategi Pelanggan Melalui Inovasi CRM dan Kualitas Produk: Dampaknya terhadap Loyalitas di Nou Coffee Shop - Roseline roseline; Hommy Dorthy Ellyany Sinaga; Edwin Sugesti Nasution (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
Nou Coffee is a local coffee shop in Medan adopts a modern, fast, efficient, and digitally integrated concept to deliver high-quality coffee. However, consumer loyalty has recently declined, indicated by fewer repeat visits and reduced digital interactions. The implementation of Customer Relationship Management (CRM) has often been less effective due to its generalized interactions, highlighting the need for more personalized, data-driven communication to strengthen relationships with consumers. In addition, product quality remains a key factor in building loyalty, including aspects such as taste, consistency, hygiene, raw materials, and comfort. Although Nou Coffee already uses high-quality coffee beans and a digital system, some customers perceive the taste and presentation consistency as unstable. This indicates that product quality is still the primary key to maintaining customer satisfaction and loyalty, even more important than technological convenience. The study employed a descriptive quantitative method. The population consisted of all consumers who had made purchases at Nou Coffee, totaling 10,122 customers. Using Slovin’s formula with a 95% confidence level and a 5% margin of error, the sample size was determined to be 385 respondents. The conclusion drawn from this research is that both partially and simultaneously, Customer Relationship Management (CRM) and Product Quality significantly influence consumer loyalty at Nou Coffee Shop.